2013
DOI: 10.14507/epaa.v21n7.2013
|View full text |Cite
|
Sign up to set email alerts
|

Value-added Teacher Estimates as Part of Teacher Evaluations: Exploring the Effects of Data and Model Specifications on the Stability of Teacher Value-added Scores

Abstract: If teacher value-added estimates (VAEs) are to be used as indicators of individual teacher performance in teacher evaluation and accountability systems, it is important to understand how much VAEs are affected by the data and model specifications used to estimate them. In this study we explored the effects of three conditions on the stability of VAEs and evaluated their relative impact. We varied how we accounted for differences among students in their prior learning; whether we epaa aapeValue-added teacher es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…It also showed that the correlations for teachers from year-to-year significantly varied by subject matter, posing additional concerns about the fairness of VAM for all teachers. Furthermore, since we do not have sufficient information about the model, we are left with the myriad concerns related to model specification and fit that are prevalent in the research on VAM (e.g., Amrein-Beardsley, 2008;Goldhaber et al, 2013;Hill et al, 2011;Kersting et al, 2013;Schochet& Chiang, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also showed that the correlations for teachers from year-to-year significantly varied by subject matter, posing additional concerns about the fairness of VAM for all teachers. Furthermore, since we do not have sufficient information about the model, we are left with the myriad concerns related to model specification and fit that are prevalent in the research on VAM (e.g., Amrein-Beardsley, 2008;Goldhaber et al, 2013;Hill et al, 2011;Kersting et al, 2013;Schochet& Chiang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research on VAM has consistently found issues that should give pause to policymakers implementing VAMs for evaluative purposes. Studies have shown there are myriad concerns with the validity of VAM due to issues with model specification (e.g., Amrein-Beardsley, 2008;Goldhaber et al, 2013;Hill et al, 2011;Kersting et al, 2013;Schochet& Chiang, 2011) as well as the validity threats posed by other matters like test selection and timing (Papay, 2011). Bearing this body of research in mind, it is critical for state policies regarding VAM to be closely scrutinized.…”
mentioning
confidence: 99%
“…Although I recognize that students' performance can be measured in various ways, such as students' efficacy (Griggs, Rimm-Kaufman, Merritt, & Patton, 2013;Jansen, Scherer, & Schroeders, 2015) and via nontraditional assessment methods (Robinson, Dailey, Hughes, & Cotabish, 2014), academic student achievement data has implications for teacher evaluations (Berliner, 2013;Kersting, Chen, & Stigler, 2013), district funding (Niven, Holt, & Thompson, 2014;Ostrander, 2015), and public perceptions of effective teaching and learning (Popham, 1999). Therefore, for this paper, I define student achievement in terms of how students score on standardized tests.…”
Section: Academic Achievement In Urban Schoolsmentioning
confidence: 99%
“…Las estimaciones del efecto profesor han resultado atractivas, debido a lo intuitivo de su interpretación, al estar directamente relacionadas con mediciones de aprendizaje, y debido al amplio rango de desempeño identificado, en comparación con mediciones de calidad basadas en criterios de desempeño profesional, que se caracterizan por resultados más homogéneos (Kersting, Chen & Stigler, 2013;Milanowski, 2011, Abril).…”
Section: Medidas De Valor Agregadounclassified
“…En este modelo el efecto del profesor corresponde a la predicción del efecto aleatorio μ oj , término que captura la diferencia entre el desempeño estimado de los alumnos de un profesor y el desempeño observado para ese grupo de alumnos. Si bien esta conceptualización se ha utilizado en otros estudios (Kersting et al, 2013;Newton et al 2010), es importante explicitar que podría contar con un problema de endogeneidad en la estimación (para más detalles ver Manzi, San Martin & Van Bellegem, 2014). El análisis de estabilidad de las estimaciones se realiza mediante la comparación de modelos de dos niveles que incorporan progresivamente diversas variables, primero en el nivel del alumno y luego en el nivel del profesor/sala de clases.…”
Section: Estimación Del Efecto Profesor En Un Modelo De Dos Niveles Yunclassified